PREVALENCE AND SEVERITY OF OBSTRUCTIVE SLEEP APNEA IN PATIENTS WITH COPD UNDERGOING OUTPATIENT PULMONARY REHABILITATION: A LITERATURE REVIEW - Souza, Shayra Kellen Arantes; Queiroz, Luiz Felipe Elias de; Aguiar, Brunna Ferreira; Oliveira, Ananda Camille Silva; Oliveira, Miriã Cândida; Oliveira, Luís Vicente Franco de (CIPEEX, 2025)
Introduction: Chronic obstructive pulmonary disease (COPD) and obstructive sleep apnea (OSA) are significant respiratory conditions with a global impact on public health. COPD leads to chronic inflammation and breathing difficulties, while OSA, characterized by episodes of apnea and hypopnea, affects sleep quality. Objective: To review the literature to understand the severity and prevalence of OSA in patients with COPD undergoing pulmonary rehabilitation (PR). Methodology: Three clinical trials were extracted from the PubMed database, published between 2015 and 2024. The Health Sciences Descriptors (DeCS) used for the search were: “chronic obstructive pulmonary disease,” “obstructive sleep apnea,” “rehabilitation,” “prevalence,” and “severity,” in English and Portuguese, with the Boolean operator “AND.” The inclusion criteria were publications in Portuguese and English, original studies, and free access. Results: OSA is prevalent among patients with COPD, with variations in the severity of respiratory disorders, and PR has been shown to demonstrate benefits in quality of life and control of the overlap syndrome. However, factors such as body mass index and comorbidities also influence the severity of COPD. Conclusion: The association between COPD and OSA is common and negatively affects patients' quality of life, and PR offers significant improvements; however, further studies are needed to strengthen the evidence and seek scientific consensus.